Fabrication of flexible, and bioresorbable poly-l-lactide acid piezoelectric material with tunable properties. (2022) - Merhi, Youssif; Agarwala, Shweta
Abstract: There is a clinical need for the development of sensors to measure buildup of pressure on organs, as it is indicative of many underlying ailments. However, electronic devices need to be flexible, and have low Young's modulus to be compatible with human tissues. Although many advances have been made in bioresorbable devices making these devices with safe materials and simple processes remains a challenge. Here, we propose a simple and scalable method of fabricating biocompatible as well as bioresorbable piezoelectric poly-l -lactide acid (PLLA) based films. Films which will be used to fabricate force sensors. Our strategy focuses on material processing to improve crystallinity and orientation of polymer chains to achieve a good piezoelectric response.